Improvement and Experimental Study of Loading Mode of Vacuum Preloading Method - WEI Yanbing; LI Zhenxin; LI Yao (Renmin Zhujiang)
For the phenomenon of “soil column” occurred in the reinforcement of mud by vacuum preloading method,in order to improve the reinforcement effect of vacuum preloading this paper summarizes and analyzes the formation mechanism of “soil column” for coming to the conclusion that the main reason for the formation of “soil column” is the silting of drainage board,proposes the method of step vacuum loading,concludes that the strength of reinforced soil increases largely under the step vacuum loading method after analysis of the theory of soil mechanics,and verifies it through the indoor model test.The results show that the permeability coefficient of the plastic drainage board decreases slightly and the consolidation settlement value of the reinforced mud is larger under the step vacuum loading,indicating that the step vacuum loading method can reduce the silting of drainage boards,delay the occurrence of “soil column” phenomenon,and improve the overall reinforcement effect of mud.